Relationship Between Breastfeeding Self Efficacy and Exclusive Breastfeeding At Posyandu Working Area Of Pacarkeling Puskesmas Surabaya - Elisa Cahyaningtyas, Fabella; Fitriana, Farida; Tri Arif Sampurna, Mahendra (Rifa'Institute, 2022)
Background: Breast milk is the main and best food for babies, it contains essential nutrients and antibodies that babies need for their growth and development. Exclusive breastfeeding is an indicator listed in the Strategic Plan of the Ministry of Health for the period 2020-2024, even in the Strategic Plan of the previous period (2015-2019) in the performance indicators (IKK) of the Directorate of Community Nutrition, because it is closely related to the government's priority program, namely the acceleration of stunting reduction which was achieved 11 .6% of the target of 24.1%. The percentage of infants aged 0-6 months who received exclusive breastfeeding was 66.1% of the 40% target. (Ministry of Health, 2020). Even though this figure has met the national target, efforts to increase exclusive breastfeeding coverage must still be carried out as an effort to reduce stunting in Indonesia. Breastfeeding self-efficacy is a factor that can influence mothers to give exclusive breastfeeding to their babies. Methods and Samples: This research is a type of quantitative research, namely observational analytic using a case control approach. The number of samples is 69 respondents. The sampling technique used purposive sampling technique which was determined based on the right criteria. Results: The results of statistical tests get a p value of 0.038, p value <0.05, meaning H0 is rejected, H1 is accepted with an Odd Ratio value of 4.981. Conclusion: There is a relationship between self-efficacy of breastfeeding mothers and exclusive breastfeeding in the Posyandu Work Area of ??the Surabaya Boyfriend Health Center